2022
DOI: 10.3389/fendo.2022.970122
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose index is associated with cerebral small vessel disease burden and cognitive impairment in elderly patients with type 2 diabetes mellitus

Abstract: ObjectiveTo investigate the relations of Triglyceride glucose (TyG) index with cerebral small vessel disease (CSVD) burden and cognitive function in aged patients with type 2 diabetes mellitus (T2DM).MethodsA total of 308 elderly patients with T2DM were included in this retrospective study. The standardized Chinese version of Mini-Mental State Examination was used to assess cognitive function. The total CSVD burden score was assessed by combining four imaging markers of CSVD, including the presence of white ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“… 22 Another recent cross-sectional study of the elderly aged 60 years and older indicated that the TyG index is an independent risk factor for cognitive impairment and severe cerebral small vessel disease burden in elderly patients with T2D. 23 As we mentioned earlier, cognitive impairment appears to develop earlier in T2D patients. Therefore, this study provides a possibility for the identification of MCI in patients aged 40 years and older with T2D.…”
Section: Introductionmentioning
confidence: 83%
“… 22 Another recent cross-sectional study of the elderly aged 60 years and older indicated that the TyG index is an independent risk factor for cognitive impairment and severe cerebral small vessel disease burden in elderly patients with T2D. 23 As we mentioned earlier, cognitive impairment appears to develop earlier in T2D patients. Therefore, this study provides a possibility for the identification of MCI in patients aged 40 years and older with T2D.…”
Section: Introductionmentioning
confidence: 83%
“…Triglyceride-glucose (TyG) index, denoted ln [triglycerides (TG) (mmol/L) * fasting blood glucose (FBG) (mmol/L)/2], is a simple and reliable surrogate marker of insulin resistance [9]. Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 Total CSVD burden scores ≤2 were classified as mild CSVD burden and above 2 categorized as severe CSVD burden. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%
“…25,26 Total CSVD burden scores ≤2 were classified as mild CSVD burden and above 2 categorized as severe CSVD burden. 27,28 304 24 items were used to assess anxiety or depression. According to previous studies, 29 the diagnosis of cognitive impairment was based on the optimal cut-off scores of MoCA: 0-13 for illiterate, 0-19 for 1-6 years of education, 0-24 for 7 or more years of education for Chinese adults.…”
Section: Assessment Of Total Csvd Burden Scoresmentioning
confidence: 99%